Pesticide Fires - Frederick M. Fishel (EDIS)
PI223, a 7-page illustrated fact sheet by Frederick M. Fishel, introduces the potential problems associated with pesticide fires, precautions to take, what to do if a fire occurs, and a table to decode the numbers on the diamond-shaped National Fire Protection Association warning symbol. Includes form for pre-fire plan and additional sources of information. Published by the UF Department of Agronomy, October 2009.